Sosialisasi Pemilihan Umum yang Damai di Desa Allang Asaude - Laury Marcia Ch. Huwae; Ronald Darlly Hukubun; Marlin C. Wattimena; Lusanra Jacqueline Tutkey; Ratih C. F. Ratumanan (ABDISOSHUM: Jurnal Pengabdian Masyarakat Bidang Sosial dan Humaniora, 2025)
The socialization of peaceful elections in Allang Asaude Village, West Seram Regency – Maluku Province, aims to create a common understanding among the community to become smart and responsible voters, as well as the importance of maintaining security and peace during the election process. This program is implemented to support peaceful elections, prevent potential conflicts and the spread of provocative information or hoaxes that can disrupt village social stability. It also provides education to novice voters regarding voting rights to choose leaders who serve the community, as well as avoid money politics. The socialization stage is divided into 3 parts, namely the preparation stage (coordination with village officials and the preparation of socialization materials), the implementation stage (material presentation), and the last stage (evaluation and documentation). The results of the activity showed an increase in public awareness of the importance of peaceful elections, a willingness to avoid provocative actions, and a joint commitment to maintaining a harmonious atmosphere during the elections. Through this socialization, it is hoped that Allang Asaude Village will be able to become an example of a village that prioritizes the principles of peaceful and democratic elections, as well as supporting the 2024 regional head elections later.